SUASANA PEMBELAJARAN DAN MUTU PELAKSANAAN PERKULIAHAN ENGLISH FOR BIOLOGY II PROGRAM PGMIPA-UNGGULAN FKIP UNIVERSITAS RIAU - Darmadi Ahmad; Firdaus L.N (Biogenesis, 2013)
A descriptive study on learning atmosphere in the excellence Biology Teacher’s Education Program, The Faculty of Teacher Training and Education, University of Riau has been conducted in the Even Semester of the Academic Year 2012/2013. The objective was to find out the learning atmosphere in English for Biology II courses. As much as eighteen students have been defined as the total respondents by total sampling technique. Data of seven indicators learning atmosphere, namely: (1) cohesiveness, (2) lecture support, (3) involvement, (4) investigation, (5) task orientation, (6) cooperation, and (7) lecture equity obtained by questionnaire What Is Happening In this Class (WIHIC). The questionnaire was valid (rxy0,54>critical values0,3) dan reliabel (r110,96>critical values0,7). The questionnaires were directly distributed to the respondents at the end of the semester. Supplements data were taken by video recording during the learning process. All data were analyzed descriptively. The results showed that learning atmosphere English for Biology II were considered very conducive from aspects of cohesiveness of relationship between students, task orientation, cooperation and lecture equity. While the lecture support, involvement, and student investigations were considered is enough conducive. In conclusion, the learning atmosphere of English for Biology II by using Researchbased teaching were considered was enough conducive. However, the learning atmosphere of English for Biology II is still needs to be improved in order to become very conducive, especially with regard to indicators of lecturer support, student involvement and investigation.Keywdors: excellence biology teacher education programs, english for biology II course, learning atmosphere, research-based teaching